2014
DOI: 10.1364/oe.22.024348
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic shift of surface plasmon resonance of gold nanoparticles doped in nematic liquid crystal

Abstract: Study of the liquid crystal (LC) director around nanoparticles has been an important topic of research very recently, since it allows design and fabrication of next-generation LC devices that are impossible in the past. In our experiment, alkanethiol-capped gold nanoparticles (GNPs) were dispersed in nematic LC. Analysis of the LC director around GNPs was performed by investigating the behavior of surface plasmon polariton (SPP) absorption peaks of the GNPs using spectrophotometry technique. It is found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The application of LCs includes metamaterials [4], photonic crystals [5], plasmonic structures [6], THz devices [7], sensors [8], diffractive optics [9], adaptive lens technologies [10] and vision correction [11], as well as tunable filters [12] and dispersion for imaging [13]. In addition, nanoparticles can induce other new functions in liquid crystals, including improved response time [1415], surface plasmon resonance [16], and improvements in alignment [17]. …”
Section: Resultsmentioning
confidence: 99%
“…The application of LCs includes metamaterials [4], photonic crystals [5], plasmonic structures [6], THz devices [7], sensors [8], diffractive optics [9], adaptive lens technologies [10] and vision correction [11], as well as tunable filters [12] and dispersion for imaging [13]. In addition, nanoparticles can induce other new functions in liquid crystals, including improved response time [1415], surface plasmon resonance [16], and improvements in alignment [17]. …”
Section: Resultsmentioning
confidence: 99%
“…The conducting electrodes are designed using a transparent indium-tin-oxide (ITO) thin film deposited on a glass substrate. A desired pattern of the ITO electrode can be carved using photolithography techniques [ 44 , 55 , 56 , 57 , 58 , 64 ]. In order to achieve alignment of the NLC molecules, one needs to pre-treat these electrodes with appropriate chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…Such structures could be like Saturn rings, boojams, and hedghogs, which have been studied both theoretically and experimentally, showing the dependence on their size and shape [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The anisotropic molecular alignment around gold nanoparticles (GNPs) has been verified in experimental observations of NLC materials [ 44 ]. The addition of GNPs in NLCs has shown a remarkable red shift of the surface plasmon polaritons (SPP) peak in the absorption spectra of NLC/GNP composite systems due to an increment in the refractive index of an NLC when light is polarized parallel to the director of the NLC [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…[23] Theo bserved anisotropic plasmon damping may thus result by anisotropic thermal conductivity (phonon diffusion) in the host MOF matrix as it is expected that for the Cu 2 (BPYDC) 2 MOF the thermal conductivity is larger along b-axis (pore direction). [24] Theo bserved shift in the plasmon resonance peak to longer wavelengths with increasing angle between light polarization and a-axis of Cu 2 (BPYDC) 2 likely results from dielectric constant anisotropy of MOF matrix [25] as it is well-known that plasmon resonance wavelengths are longer when metal nanoparticles are accommodated in am atrix with larger dielectric constants. [26] Thep recise alignment of this MOF-on-MOF system allows for the plasmon resonance of guest Ag NPs to be modulated by changing the orientation of the MOF thin film.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[22] Figure 5b shows the polarization-dependent UV/Vis absorption spectra measured with an integrated sphere in areflection mode.The difference absorption spectra before and after the Ag NPs impregnation are also shown in Figure 5c.W en ote there are two types of polarization-dependent changes in the plasmon resonance of Ag NPs:plasmon damping and peak shift. [24] Theo bserved shift in the plasmon resonance peak to longer wavelengths with increasing angle between light polarization and a-axis of Cu 2 (BPYDC) 2 likely results from dielectric constant anisotropy of MOF matrix [25] as it is well-known that plasmon resonance wavelengths are longer when metal nanoparticles are accommodated in am atrix with larger dielectric constants. 400-500 nm (Figure 5b)c learly decreases when the angle between the aaxis of MOF and the light polarization increases from 08 8 to 908 8.P revious reports indicated that the damping of plasmon resonance can take place through an electron-phonon interaction.…”
mentioning
confidence: 99%